Analysis of handover performance in mobile WiMAX networks / Noor Nabila Huda Yacob - Yacob, Noor Nabila Huda (2013)
Mobile terminals allow users to access service while on the move. This unique feature has driven the rapid growth in the mobile network industry, changing it from a new technology into a massive industry in less than two decades. The handover performance in mobile network is the most important factor that can influence the Quality of Service (QoS). Nowadays, many countries in the world have move to more advance mobile communication system such as IEEE 802.16e Mobile WiMAX standard. The parameters such as handover time, throughput and packet delay are the main factors which affect the mobile WiMAX network performance. OPNET 14.5 is used to simulate the mobile WiMAX handover process.